Effectiveness of Telenursing in the Management of Type 2 Diabetes Mellitus in the Elderly: A Scoping Review - Agnes Epiphania Dua; Desi Novitasari; Fadila Lam; Faisal Adi irawan; Ike Ayunda Nasifah; Jimni Maulana; ⁠Kartika Milaningrum; Lailatul Badriah; Maria Jia Fernandez; Ninik Dwi Rahayu; Retno Indarwati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Type 2 Diabetes Mellitus (T2DM) results from insulin resistance and is linked to obesity, which accounts for 80% of diabetes cases. The elderly are particularly vulnerable, facing high treatment costs and self-care challenges, including blood sugar monitoring and diet adherence. Complications include hypoglycemia, neuropathy, and cardiovascular diseases. Telenursing is a promising intervention that enhances adherence and provides remote education. However, further research is needed to assess its long-term effectiveness. Objective: this study aims to assess the effectiveness of telenursing in managing type 2 diabetes mellitus in the elderly. Method: This scoping review follows the PRISMA-ScR guidelines, analyzing studies from ProQuest, PubMed, and Scopus. Inclusion criteria focused on studies evaluating the impact of telenursing on elderly patients with T2DM using quantitative or mixed-method approaches. Results: From 716 screened articles, seven met the inclusion criteria. Most studies were conducted in Iran, Saudi Arabia, and Slovenia, with one multinational study involving ten countries. Six studies employed quantitative methodologies, including randomized controlled trials and clinical studies. Findings indicate that telenursing significantly improves medication adherence, blood glucose control, and self-management. It reduces the need for in-person visits and enhances patient education, leading to better glycemic control and lower complication risks. Conclusions: Telenursing proves to be an effective approach for managing T2DM in the elderly, promoting adherence and self-care while reducing healthcare facility visits. Further research is required to evaluate its long-term sustainability and effectiveness.